On Almost Orthogonal Frames - Virender; A. Zothansanga; S. K. Kaushik (International Journal of Mathematics and Mathematical Sciences)
Almost orthogonal frames have been introduced and studied. It has been proved that a bounded almost orthogonal frame satisfies Feichtinger conjecture. Also, we prove that a bounded almost orthogonal frame contains a Riesz basis.